Histopathological hoof laminar changes in horses with Pituitary Pars Intermedia Adenoma: Cases report - Laskoski, L. M.; Locatelli Dittrich, R.; Valadão, C. A.A. [UNESP]; Castro, M. L.; Araujo, F. F.; Silva, J. R.; Basso, F. Z.; Dornbusch, P. T.; Deconto, I.; Sousa, R. S. (FapUNIFESP (SciELO), 2015)
Laminitis in horses is often associated with endocrine disorders, especially the pituitary pars intermedia dysfunction (PPID) in older animals. Morphologic exams of the laminar tissue of the hoof were performed in two horses with suspected PPID, with no clinical signs of laminitis. Changes compatible with laminitis of endocrine origin were observed, such as rounding of the nuclei of the basal cells, thinning and stretching of the secondary epidermal laminae and tissue proliferation. PPID horses with no clinical signs of laminitis may be affected by lesions of the laminar tissue of the hoof that compromise the integrity of the dermal-epidermal junction and may develop clinical symptoms of the disease. It has been suggested that the development stage of endocrine laminitis is longer, but further studies should be conducted to confirm it.
Keywords: Cushing's syndrome; Endocrine disorders; Laminitis; Metabolic syndrome; Pituitary adenoma